Review, classification and loss comparison of modular multilevel converter submodules for HVDC applications - Tian, Yumeng (2022)
The circuit topology of a submodule (SM) in an modular multilevel converter (MMC) defines many of the functionalities of the complete power electronics conversion system and the specific applications that a specific MMC configuration can support. Most prominent among all applications for the MMC is its use in high-voltage direct current (HVDC) transmission systems and multiterminal dc grids. The aim of the paper is to provide a comprehensive review and classification of the many different SM circuit topologies that have been proposed for the MMC up to date. Using an 800-MVA, point-to-point MMC-based HVDC transmission system as a benchmark, the presented analysis identifies the limitations and drawbacks of certain SM configurations that limit their broader adoption as MMC SMs. A hybrid model of an MMC arm and appropriate implementations of voltage-balancing algorithms are used for detailed loss comparison of all SMs and to quantify differences among multiple SMs. The review also provides a comprehensive benchmark among all SM configurations, broad recommendations for the benefits and limitations of different SM topologies which can be further expanded based on the requirements of a specific application, and identifies future opportunities.